2004
DOI: 10.1007/s10157-003-0267-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous remission of persistent severe hematuria in an adolescent with nutcracker syndrome: seven years? observation

Abstract: A Japanese boy aged 14 years presented with gross hematuria associated with mild proteinuria and was diagnosed as having nutcracker syndrome. Magnetic resonance angiography (MRA) revealed significant compression of the left renal vein between the aorta and the superior mesenteric artery with collaterals. A percutaneous renal biopsy on the right kidney revealed no evidence of glomerular or interstitial changes with immune deposition. He was observed closely without any intervention thereafter. Although repeat M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 7 publications
1
34
0
5
Order By: Relevance
“…Recently, Tanaka et al described an adolescent with nutcracker syndrome who showed spontaneous remission of persistent severe hematuria after 7 years' observation, and suggested that his good physical development, especially the increase in height, might be the cause of the spontaneous remission of the disease [7]. We were interested in this point and investigated the natural course and outcome of nutcracker syndrome using Doppler US.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, Tanaka et al described an adolescent with nutcracker syndrome who showed spontaneous remission of persistent severe hematuria after 7 years' observation, and suggested that his good physical development, especially the increase in height, might be the cause of the spontaneous remission of the disease [7]. We were interested in this point and investigated the natural course and outcome of nutcracker syndrome using Doppler US.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Tanaka et al reported that spontaneous remission of persistent severe hematuria occurred in an adolescent with nutcracker syndrome after 7 years' observation, and suggested that his good physical development might change the presumptive hemodynamic factors [7]. The purpose of this study was to identify factors affecting spontaneous resolution of hematuria in children with nutcracker syndrome.…”
Section: Introductionmentioning
confidence: 97%
“…year-old patient in whom spells of gross hematuria did not remit until 4 years after diagnosis [7]. Invasive procedures such as stenting or surgical correction are usually reserved for patients with intractable pain or significant episodes of blood loss requiring transfusions [2,3,20].…”
mentioning
confidence: 99%
“…In males, back pressure into the left gonadal vein may also lead to a left-sided varicocele [1][2][3]. Children and adolescents with Nutcracker syndrome usually develop hematuria like adults [5][6][7][8], but may also present with orthostatic proteinuria [9] or intussusception [10].…”
mentioning
confidence: 99%
“…7 schlanke (asthenische) Kinder bzw Jugendliche. Es liegen Studien vor, in denen durch Gewichtszunahme ein Sistieren des Nut crackerPhänomens beobachtet wurde[11]. Patient eine Einschränkung der Nierenfunktion, eine Proteinurie oder z.…”
unclassified